Effect of cholecalciferol on immune and vascular function in non-diabetic chronic kidney disease - Kamboj, Kajal; Pariki, Aruna; Singhal, Manphool; Lal, Anupam; Naik, Sachin; Kumar, Vivek; Yadav, Ashok Kumar; Jha, Vivekanand (Frontiers in Immunology, 2025)
Background and aimsVitamin D deficiency, widely prevalent in patients with chronic kidney disease (CKD) could play a role in the pathogenesis of cardiovascular disease (CVD) by causing alterations in endothelial and immune function. We investigated the change in immune and vascular functions following vitamin D supplementation in non-diabetic subjects with stage 3-4 CKD and vitamin D deficiency.MethodsIn this single-arm study, non-diabetic CKD subjects aged 18–75 years, eGFR 15-60 ml/min/1.73m2, and serum 25-hydroxyvitamin D3 levels <20 ng/ml were enrolled. Enrolled subjects received a directly observed oral dose of 300,000 IU cholecalciferol at baseline and 8 weeks. Outcome assessments, including immunological, vascular, endothelial, inflammatory, and biochemical parameters, were measured at baseline and 16 weeks.ResultsIn total, 62 subjects were studied. The mean age was 44 ± 12 years with 58% men. TH1 cells decreased from 17% (9%, 27%) to 11% (6%, 16%) (p=0.002) and TH2 cells increased from 9% (5%, 16%) to 16% (10%, 27%) (p=0.001) after cholecalciferol treatment. A significant increase in mRNA expression of vitamin D-responsive genes (cathelicidin, IL-10, VDR, and CYP27B1) was observed. The levels of pro-inflammatory cytokines (IFN-γ, TNF-α, IL-23, and IL-6) decreased whereas anti-inflammatory cytokines (IL-4, IL-10, and IL-13) showed an increase. Cholecalciferol treatment improved flow-mediated dilatation (FMD): 8.2% (6.2%, 12.1%) at baseline to 14.1% (10.0%, 20.1%) at 16 weeks (p<0.001).ConclusionsThis study confirms that cholecalciferol supplementation influenced immune function as it favored the TH2/TH1 phenotype, favorably affected the levels of inflammatory markers and mRNA expression of vitamin D responsive genes, and improved vascular function in CKD.Clinical Trial Registrationhttps://www.ctri.nic.in, identifier CTRI/2019/10/021494.